Clinical and Anatomical Factors Affecting Recurrent Laryngeal Nerve Paralysis During Thyroidectomy via Intraoperative Nerve Monitorization - Aygun, Nurcihan; Kostek, Mehmet; Unlu, Mehmet Taner; Isgor, Adnan; Uludag, Mehmet (Frontiers in Surgery, 2022)
Background: Despite all the technical developments in thyroidectomy and the use of intraoperative nerve monitorisation (IONM), recurrent laryngeal nerve (RLN) paralysis may still occur. We aimed to evaluate the effects of anatomical variations, clinical features and intervention type on RLN paralysis. Method: The RLNs identified till the laryngeal entry point, between January-2016 and September-2021, were included in the study. The effects of RLN anatomical features considering the International RLN Anatomical Classification System, intervention and monitoring types on RLN paralysis were evaluated. Results: 1412 neck sides of 871 patients (672F, 199M) with mean age of 49,17+13,42 years (range, 18-99) were evaluated. Eighty-three nerves (5.9%) including 78 nerves with transient (5.5%) and 5 (0.4%) with permanent vocal cord paralysis (VCP) were detected. The factors that may increase the risk of VCP were evaluated with binary logistic regression analysis. While the secondary thyroidectomy (OR:2.809, 95%CI: 1.302-6.061, p=0.008) and Berry entrapment of RLN (OR:2.347, 95%CI:1.425-3.876, p=0.001) were detected as the independent risk factors for total VCP, the use of intermittent-IONM (OR:2.217, 95%CI:1.299-3.788, 0.004), secondary thyroidectomy (OR:3,257, 95%CI: 1.340-7.937, p=0.009), and nerve branching (OR:1.739, 95%CI:1.049-2.882, p=0,032) were detected as independent risk factors for transient VCP. Conclusion: Preferrance of continuous-IONM particularly in secondary thyroidectomies would reduce the risk of VCP. Anatomical variations of the RLN cannot be predicted preoperatively. Revealing anatomical features with careful dissection may contribute to risk reduction by minimizing actions causing traction trauma or compression on the nerve.